ANALISIS KEPUTUSAN PEMBELIAN PRODUK INVESTASI REKSA DANA PADA APLIKASI FINTECH "BIBIT" - Aulia Riskia (2022)
This study was conducted to determine and analyze the effect of sales promotion and social media marketing on purchasing decisions for mutual fund investment products in the fintech Bibit application partially and simultaneously. This type of research is quantitative and uses primary data sources. The object of this research is the user of the Bibit fintech application. The number of samples used were 100 respondents who were selected by accidental sampling technique. Data analysis used descriptive and inferential analysis techniques. Data were collected through questionnaires and tested using the PLS (Partial Least Square) statistical test tool. The results of the test show that: (1) purchasing decisions are influenced by sales promotions, (2) purchasing decisions are also influenced by social media marketing, (3) purchasing decisions are simultaneously influenced by sales promotions and social media marketing. From the results of the study, it is better for the Seeds to be able to implement sales promotions well and improve social media marketing to be able to encourage purchasing decisions for users of the Bibit application.